Foreign Expenditures in the Umayyad Dynasty in Andalusia - Osama I. Hammadi; Fwaaz Z. Jazae (مجلة جامعة الأنبار للعلوم الإنسانية, 2021)
Research Summary This study came to shed light on the external expenditures in Andalusia during the era of the Umayyad state. The Umayyad princes spent various expenditures that were the outcome of the balance of the public treasury revenues. These expenditures began in the era of the emirate (138-316 AH / 756-929 CE), but these expenditures increased dramatically in the era of the caliphate (316-422 AH / 929-1031AD) due to the development it witnessed in many aspects, especially the economic side, where the Andalusian gold coins were I found the best proof of this in the Kingdom of Navarre